Gambaran Implementasi Program Safety Observation Tour Dengan Model Countenance di PT Pelabuhan Indonesia II (Persero) Cabang Banten Tahun 2019 - Hartomy, Eka; Farid, M. (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Pelindo II Banten designed the safety observation tour program as an unsafe act andunsafe condition supervising program at the workplace. This program is targeted torelease monthly reports. However, this program only released monthly reports in April2018, April-May 2019, and September 2019, so the results did not fulfill the target. The objective of this study was to describe the implementation of a safety observation tour program in PT Pelabuhan Indonesia II (Persero) Banten Branch. This study wasconducted from December 2019 to June 2020 using the qualitative method and thecountenance model for program evaluation. The informant of this study was chosenusing a purposive sampling method. Triangulation techniques in this study used sourcetriangulation and method triangulation. According to the countenance model forevaluation, the results of this study were on intended antecedent, intended transaction, and intended outcomes aspects; not all aspects of the program are planned. Not all aspects of the program were realized based on observed antecedents, observed transactions, and observed outcomes. Not all aspects of the program fulfill the standards. Recommendations that can be given were to hold training for the safetyobservation tour program, complete the facilities for the program, complete the policyand procedure aspects of the program, improve the program implementation, improvethe follow-up aspects of the safety observation tour program, and improve the monthlyreport aspects of the program.Keywords: Countenance model, OHS hazard reporting, Safety observation tour